Effects of drying methods on the quality parameters of dried manis Terengganu melon (Cucumis melo) - Norlia, Muhamad; Nurul Adillah, Mohd Redzuan (2019)
The objective of this study was to identify the suitable drying methods for preservation of immature Manis Terengganu melon by using different temperatures which are 40 °C, 50 °C and 60 °C. The osmotically pretreated samples were dried by using three types of convective dryer; cabinet dryer, oven dryer and rotary dryer. The drying time and drying rates were determined through drying curve. Rotary dryer had the shortest drying time and drying rates followed by cabinet dryer and oven dryer. The quality parameters on dried melon were identified. The range of water activity achieved for dried melon was 0.46-0.52. The hardness and chewiness of dried melon showed significantly difference between fresh and dried sample. The browning absorbance of dried melon at 420 nm for each equipment at temperature 50 °C showed significant difference at p<0.05. Rotary dryer at 50 °C was preferred as the suitable drying equipment to dry melon in terms of time consumption as well as produced acceptable physicochemical quality of dried melon.